Grain losses in the mechanized harvest of upland rice as a function of speed displacement and reel - Reis, Elton Fialho; Borges, Greice Resende; da Silva, Jose Geraldo; de Oliveira, Jaison Pereira (Comunicata Scientiae, 2013)
The mechanical harvesting has been experimenting great technological evolution, in search of minimizing the losses that they can be avoided partially, being taken some tuning attentions. The objective of this work was to determine the losses of grain in the moment of the harvest in function of velocities, the reel of the harvester. An experiment was performed in the Abadiânia - Goiás, following a completely randomized design, factorial scheme 4x4, four-speed operation Vo1 = 2.6 km h-1, Vo2 = 3.3 km h-1, Vo3 = 5.0 km h-1 and Vo4 = 6.4 km h-1 and four speeds of the reel, 9%, 16%, 23% and 29% higher than the speed of the machine, with three replications. Were determined to cut losses of the platform, internal mechanisms and total harvest. Seeds were harvested with moisture of 18% w.b. The results were submitted to analysis of variance at 5% probability and operated using the correspondence analysis (CA). The results concluded: i) the analyzed losses are close of the acceptable limit, ii) the interaction between the operation speed and of the reel interferes on the losses provoked by the court platform, and iii) the analysis for correspondence allowed to analyze the relation between the operation speed and of the reel of the harvesters, in the determination of the losses of grains.